STUDY OF THE USAGE OF FERMENTED CHICKEN MANURE MEDIA ON MOINA sp. CULTURE - Yulintine; Putri Pandiangan; Uras Tantulo; Erniaty (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
The study was conducted to determine the use of EM-4 (Effective Microorganism-4) probiotics on the fermentation of chicken manure as fertilizer on the population growth of Moina sp. This study used the RAL (Completely Randomized Design) method with 4 treatments 3 replicates. This research was conducted for one month from December 01- 31, 2022 at UPT Laboratorium Lahan Gambut Cooperation In Sustainable Managemant Of Tropical Peatland (LLG-CIMTROP), Jalan Hendrik Timang UPR Tanjung Nyaho Campus Palangka Raya, Central Kalimantan. Four treatments were treatment A with 100 g dry chicken manure without the probiotics, treatment B with 100 g dry chicken manure and 6 ml the probiotics solution, treatment C with 100 g dry chicken manure and 12 ml the probiotics solution, and treatment D with 100 g dry chicken manure and 18 ml the probiotics solution. The results obtained that the use of chicken manure fermented by 18 ml EM-4 probiotic solution provided the highest density of Moina sp. about 800 ind/l with 75.0%/day of the population specific growth rate. However, water quality during the study was still in the normal range for the cultivation of Moina sp.